2004
DOI: 10.1080/01677060490894450
|View full text |Cite
|
Sign up to set email alerts
|

Vegf Promoter Haplotype and Amyotrophic Lateral Sclerosis (Als)

Abstract: Vascular endothelial growth factor (VEGF) is a cytokine essential for angiogenesis. A recent study found that haplotypes, determined by three SNPs (À2,578C=A, À1,154 G=A, and À634G=C) in the VEGF upstream promoter=leader sequence, were associated with risk of amyotrophic lateral sclerosis (ALS). We used samples and data from a case-control study to examine the relation of ALS to VEGF haplotype. Genotypes at each of the three polymorphic sites were determined using allele-specific primer extension reactions fol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(17 citation statements)
references
References 14 publications
2
15
0
Order By: Relevance
“…In patients with ALS, fewer motor neurons express VEGF and its receptor VEGFR-2,23 and haplotypes of three genetic variations in the VEGF gene, producing low concentrations of VEGF, increase the risk of SALS in four distinct European populations from Sweden, England and Belgium 24. In a smaller follow-up association study by Terry et al ,25 individuals homozygous for the “at-risk” variations also exhibited a threefold increased risk of ALS. In contrast, studies performed in a British, Dutch, American and, recently, Italian population reported that there was no association between VEGF haplotypes and SALS 26 27 28 29.…”
mentioning
confidence: 97%
“…In patients with ALS, fewer motor neurons express VEGF and its receptor VEGFR-2,23 and haplotypes of three genetic variations in the VEGF gene, producing low concentrations of VEGF, increase the risk of SALS in four distinct European populations from Sweden, England and Belgium 24. In a smaller follow-up association study by Terry et al ,25 individuals homozygous for the “at-risk” variations also exhibited a threefold increased risk of ALS. In contrast, studies performed in a British, Dutch, American and, recently, Italian population reported that there was no association between VEGF haplotypes and SALS 26 27 28 29.…”
mentioning
confidence: 97%
“…Research to date suggests that sporadic ALS is likely due to a combination of multiple genetic and environmental factors, which may interact in complex ways [10,11] . Putative susceptibility genes for sporadic ALS that have been supported by at least 2 studies include the vascular endothelial growth factor (VEGF) [12][13][14] , the angiogenin (ANG) [15,16] or nearby apurinic endonuclease (APEX) gene [15,17] , the hemochromatosis gene (HFE) [18,19] , the survival motor neuron genes (SMN1, SMN2) [20,21] and the cluster of paraoxonase genes on chromosome 7q (PON1, PON2, PON3) [22][23][24][25] . The PON genes are of particular interest for testing the hypothesis of gene-environment interaction in ALS since PON1 is involved in the detoxification of organophosphate pesticides and chemical nerve agents [26,27] .…”
Section: Introductionmentioning
confidence: 99%
“…One small study involving only 104 patients confirmed the findings. 124 In a Dutch population, however, no association was found, although when adding this population to the others, the association was maintained at the statistical level. 129 Three other studies (one in an Irish population and two in US populations) have been reported to be negative, but have not been published to our knowledge.…”
Section: Vegf and Human Alsmentioning
confidence: 70%
“…These polymorphisms reduce VEGF gene transcription, impair internal ribosomal entry site (IRES)-dependent translation, and interfere with translational initiation of VEGF 206 . 63,124 An association between a haplotype (AAG/AAG) and ALS was found in a Swedish population and a UK population (Birmingham-based), and in a Belgian population an association was found with the AGG/ AGG population. In another UK population (London-based), no association was found.…”
Section: Vegf and Human Alsmentioning
confidence: 96%